Education Unit’s Characteristics and Covid-19 Positivity Rate in Yogyakarta : Ecological Study - Nathaniela, Regina Marsha; Ningrum, Dina Nur Anggraini; Sutarjo, Puji (HIGEIA (Journal of Public Health Research and Development), 2023)
Abstract Limited Face-to-Face Learning (PTM Terbatas) during COVID-19 pandemic allowed interaction between populations which led to COVID-19 transmission in schools. Factors affecting the COVID-19 transmission in schools need to be known to minimize the wider spread of cases. This study aims to examine the relationship between education unit’s characteristics such as school location, educational level, school status, number of PTM participants, and health protocols implementation, to the COVID-19 positivity rate in education units in Daerah Istimewa Yogyakarta. The research design is cross-sectional ecological study with education unit as the unit analysis. Sample of 292 education units sourced from secondary data of PTM Terbatas Surveillance was analyzed univariately and bivariately with Chi-Square test. Results showed health protocols implementation (p=0.022; PR=1.657; 95% CI=1.128-2.435) had a significant relationship to the COVID-19 positivity rate. School location, educational level, school status, and the number of PTM participants had no significant relationship to the COVID-19 positivity rate. Schools with any characteristics need to encourage school communities to keep implementing health protocols to prevent COVID-19 transmission in schools. Abstrak Pembelajaran Tatap Muka (PTM) Terbatas saat pandemi COVID-19 memungkinkan terjadinya interaksi antar populasi yang menyebabkan terjadinya penularan COVID-19 di sekolah. Faktor yang mempengaruhi penularan COVID-19 di sekolah perlu diketahui untuk meminimalisir penyebaran kasus yang lebih luas. Penelitian ini bertujuan untuk menguji hubungan antara karakteristik satuan pendidikan seperti lokasi sekolah, jenjang pendidikan, status sekolah, jumlah peserta PTM, dan penerapan protokol kesehatan, terhadap positivity rate testing tracing COVID-19 pada satuan pendidikan di Daerah Istimewa Yogyakarta. Desain penelitian ini adalah cross-sectional studi ekologi dengan satuan pendidikan sebagai unit analisis. Sampel sebanyak 292 satuan pendidikan bersumber dari data sekunder Surveilans PTM Terbatas dianalisis secara univariat dan bivariat dengan uji Chi-Square. Hasil penelitian menunjukkan penerapan protokol kesehatan (p=0,022; PR=1,657; 95%CI=1,128-2,435) memiliki hubungan yang signifikan terhadap positivity rate COVID-19. Lokasi sekolah, jenjang pendidikan, status sekolah, dan jumlah peserta PTM tidak memiliki hubungan yang signifikan dengan positivity rate COVID-19. Sekolah dengan karakteristik apapun perlu mendorong warga sekolah untuk tetap menerapkan protokol kesehatan guna mencegah penularan COVID-19 di sekolah.